PELAKSANAAN PEMBELAJARAN SEJARAH SECARA DARING MENGGUNAKAN GOOGLE CLASSROOM (STUDI DESKRIPTIF TENTANG AKTIVITAS BELAJAR SISWA DI KELAS XI IPS 4 SMA KARTIKA XIX-1 BANDUNG) - Robiyana, - (2022)
Technically, the implementation of online learning is not only related to the readiness of technology and infrastructure. At the same time, there needs to be readiness from students as key parties who have an interest in the learning process. Information related to student readiness can basically be seen in detail through the learning activities they do during the learning process. This study aims to obtain an overview of student learning activities in learning history using the Google Classroom application in class XI IPS 4 SMA Kartika XIX-1 Bandung. The research method used in this study is a qualitative descriptive method. The data collection technique was done by interview, observation, and documentation study. The results of this study indicate: (1) the planning made by the teacher is still not in accordance with the conditions of student learning activities during the learning process and the evaluation process; (2) problems faced by students in optimizing learning activities are directly related to the characteristics of the Google Classroom application, teacher abilities, and their learning environment, while from teachers, problems encountered are directly related to student motivation and facilities owned by students; (3) efforts to optimize learning activities in the Google Classroom application have been carried out well by teachers and schools both in the learning process and outside the learning process. Keywords: learning activities; Online history learning; Google Classroom App